IMPROVING STUDENTS’ ABILITY IN WRITING RECOUNT TEXT BY USING RGFE HOMEWORK AND VERBAL IMAGERY - Harjono, Daud Sri; ., Regina; Husin, Syarif (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Abstract: This research aims to investigate the effectiveness of teaching writing recount text by using Routine Grammatical Features Eliciting Homework and verbal imagery. It is a pre-experimental method with one group pretest post-test design. The sample is the tenth grade students numbering 30 students. The tool of data collecting in this research is pre-test given before a treatment and written post-test given after the treatment in the form of writing recount text. The data were analyzed by effect size formula. The result of data analysis showed that the effect size of teaching writing recount text by using Routine Grammatical Features Eliciting Homework and verbal imagery is high. Key Word: RGFE Homework, Verbal Imagery. Abstrak: Penelitian ini bertujuan untuk menyelidiki keefektifan mengajar menulis teks recount dengan menggunakan Routine Grammatical Features Eliciting Homework dan verbal imagery. Metode yang digunakan adalah pre-experimental dengan dengan rancangan penelitian satu grup pre-test dan post-test. Sampel dalam penelitian ini adalah kelas X C yang berjumlah 30 siswa. Data penelitian dikumpulkan dengan memberikan test menulis seagai pre-test sebelum diberikan perlakuan dan post-test setelah diberikan perlakuan dalam bentuk menulis teks recount. Data dianalisa dengan menggunakan rumus tingkat efektifitas. Hasil penelitian menunjukkan bahwa mengajar menulis teks recount dengan menggunakan Routine Grammatical Features Eliciting Homework dan verbal imagery tingkat efektifitasnya adalah tinggi. Kata Kunci: RGFE Homework, Verbal Imagery.